2016
DOI: 10.3750/aip2016.46.4.04
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the riverbed morphology on the source of organic material and the trophic structure of fish community along the upper reaches of the Nevėžis River, Lithuania

Abstract: Čivas L., Kesminas V., Barisevičiūtė R. 2016. Impact of the riverbed morphology on the source of organic material and the trophic structure of fish community along the upper reaches of the Nevėžis River, Lithuania. Acta Ichthyol. Piscat. 46 (4): 303-312.Background. The catchment of the Nevėžis River, the sixth longest river in Lithuania, is among the most affected by agricultural activities. Although seriously disturbed by land reclamation and agricultural pollution, the Nevėžis River still has natural, anthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…of rivers supply limited information on the immanent characteristics of those water bodies (Meybeck et al 1996;Hunting et al 2017). Several researchers have shown that the hydromorphological variables such as distance from the source, slope and stream order also have an effect on fish assemblages (Olaya-Marin et al 2012;Civas et al 2016;Wolter et al 2016). Datasets for abiotic parameters are also useful to detect the behavior and fate of contaminants which may assist in developing management strategies.…”
Section: Abiotic Datamentioning
confidence: 99%
“…of rivers supply limited information on the immanent characteristics of those water bodies (Meybeck et al 1996;Hunting et al 2017). Several researchers have shown that the hydromorphological variables such as distance from the source, slope and stream order also have an effect on fish assemblages (Olaya-Marin et al 2012;Civas et al 2016;Wolter et al 2016). Datasets for abiotic parameters are also useful to detect the behavior and fate of contaminants which may assist in developing management strategies.…”
Section: Abiotic Datamentioning
confidence: 99%